Survei minat siswa SD terhadap pembelajaran PJOK pada materi senam irama di Kecamatan Ngabang - Andre, Herkulanus; Jayadi, Jayadi (Universitas Sarjanawiyata Tamansiswa, 2025)
The purpose of this study is to determine how the interest of male and female students in learning Physical Education in Sports on Rhythmic Gymnastics material in Public Elementary Schools in Ngabang District. There are 3 schools that are the place of research, namely Public Elementary School 10, Public Elementary School 1 and Public Elementary School 2. This study uses a quantitative descriptive research type. The sample in this study is at SDN 10 Ngabang totaling 29 students, SDN 2 Ngabang totaling 27 students and SDN 1 Ngabang totaling 29 students so the total number of samples is 85 students. Based on the results of the research that has been conducted, it can be seen that the interest of male and female students in learning Physical Education in rhythmic gymnastics at SDN 10 Ngabang got a score of 18.68 with a high category, the interest of male and female students in learning Physical Education in rhythmic gymnastics at SDN 2 Ngabang got a score of 15.89 with a medium category and the interest of male and female students in learning Physical Education in rhythmic gymnastics at SDN 1 Ngabang got a score of 18.09 with a high category.